The Effectiveness of Content Mastery Services with a Muhasabah Approach in Reducing Bullying Behavior in Students - Harmalis, Harmalis (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study aims to examine the effectiveness of content mastery services using a muhasabah approach in reducing bullying behavior of students at SMPN 33 Kerinci. This research is a research with a quantitative-experimental approach with a one group pretest-posttest design. The number of samples in this study were 36 students from Class VIII. The results showed that the level of students bullying behavior before the implementation of content mastery services using the muhasabah approach was mostly in the high category with an average of 131.81. After implementing content mastery services with a muhasabah approach, most were in the low category with an average of 83.72 with a decrease score of 48.08. Based on the results of data analysis using the Wilcoxon test, it shows that there is a decrease in student bullying behavior with sig. (2-tailed) of 0.001 <0.05 this indicates that ho is rejected and ha is accepted. Thus, it can be concluded that content mastery services with a muhasabah approach are effective in reducing student bullying behavior.